2015
DOI: 10.1002/ijc.29581
|View full text |Cite
|
Sign up to set email alerts
|

Apc‐driven colon carcinogenesis in pirc rat is strongly reduced by polyethylene glycol

Abstract: Polyethylene glycol (PEG) is one of the most powerful agents in reducing chemically induced carcinogenesis in rat colon. However, contrasting results in Min mice dampened the enthusiasm on this potentially strong and virtually safe, cancer chemopreventing agent. Pirc (F344/NTac-Apc am1137 ) rats carrying a germline heterozygous mutation in the Apc gene, spontaneously develop multiple tumours in the colon thus modelling both familial adenomatous polyposis (FAP) and sporadic colorectal cancer (CRC). Given this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Several groups, including our own, have replicated this work in rat the carcinogen-models [ 11 , 12 ]. Furthermore, we recapitulated these findings in genetic rodent models (MIN mouse [ 13 ] and Pirc rat [ 14 , 15 ]), which has germline truncations in the adenomatous polyposis coli (APC) tumor suppressor gene, the most common initiating driver mutation in human colorectal carcinogenesis. From a mechanistic perspective, our laboratory has demonstrated that PEG 8000 downregulated epidermal growth factor receptor (EGFR) with concomitant downregulation of SNAIL, induction of E-cadherin leading to β-catenin sequestration away from the nucleus and hence suppressing TCF/LEF-1 transcriptional activity [ 14 ].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several groups, including our own, have replicated this work in rat the carcinogen-models [ 11 , 12 ]. Furthermore, we recapitulated these findings in genetic rodent models (MIN mouse [ 13 ] and Pirc rat [ 14 , 15 ]), which has germline truncations in the adenomatous polyposis coli (APC) tumor suppressor gene, the most common initiating driver mutation in human colorectal carcinogenesis. From a mechanistic perspective, our laboratory has demonstrated that PEG 8000 downregulated epidermal growth factor receptor (EGFR) with concomitant downregulation of SNAIL, induction of E-cadherin leading to β-catenin sequestration away from the nucleus and hence suppressing TCF/LEF-1 transcriptional activity [ 14 ].…”
Section: Introductionmentioning
confidence: 92%
“…While the preclinical data provides compelling evidence of the of CRC preventive effects of PEG (~20 publications by at least 4 independent groups [ 8 , 10 , 14 , 15 ]) the only clinical data available is from a case-control study that had a number of methodological shortcomings [ 17 ]. Since epidemiological studies are often confounded by the indications for use of PEG (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This model shows a strong gender effect, with male rats developing many more tumors than do females (4). Accordingly, studies aimed at the identification of dietary components or drugs with chemopreventive activity against colonic carcinogenesis, mostly used males, which provides a stronger statistical power when assessing a reducing effect on tumorigenesis (5,6). On the other hand, female rats developing fewer intestinal tumors might be exploited for the identification of substances increasing carcinogenesis such as carcinogens present in the diet (or in toxicological studies), a possibility, to our knowledge, not tested to date.…”
mentioning
confidence: 99%